Penanaman Mangrove Sebagai Upaya Pengurangan Emisi Karbon dan Peningkatan Kesadaran Ekosistem Di kawasan Pesisir Pantai - Simarmata, Juliater; Rahmawati, Aisyah; Chaerudin, Irwan; Gultom, Simon; Simarmata, Jeremy Ephraim; Simarmata, Jean Sabastian (Institut Transportasi dan Logistik Trisakti, 2025)
The difficulties Indonesia's logistics and transportation industry faces in cutting carbon emissions in the face of rising air pollution and the destruction of coastal ecosystems are the driving force behind this community service project. As a natural remedy, mangrove planting seeks to enhance community well-being, preserve coastal ecosystems, and absorb carbon. On August 28, 2024, instructors and students from the Trisakti Institute of Transportation and Logistics participated in this activity at Jakarta's Angke Kapuk Mangrove Area. The 200 mangrove seedlings will be planted as part of the implementation strategy, which also includes socialization on the value of preserving the mangrove ecosystem and initial preparation, education, planting, and closing. The activity's outcomes demonstrated that participants were very enthusiastic and that their understanding of the importance of mangroves in mitigating climate change had grown. As a result, this project effectively met its primary objectives of lowering carbon emissions and increasing public awareness of the value of protecting the environment, creating the possibility of future conservation cooperation.